Implementasi Chatbot Pelajaran Sekolah Dasar Dengan Pandorabots - Viny Christanti; Jesslyn Jesslyn; Fundroo Orlando (UNIVERSITAS RAHARJA, 2023)
Chatbot is a virtual conversation that can receive input in the form of voice or writing. A chatbot can be a generative or retrieval chatbot. The creation of the two chatbots provides an opportunity for users to write text freely. Sometimes giving freedom to type sentences freely can result in answers that are not to the user's liking. There are several ways that users can be directed to write text in the chat column. This study aims to develop a chatbot application that can be used as a medium for questioning and answering subject matter for elementary school students in a structured manner. Chatbots developed based on AIML (Artificial Intelligence Markup Language) use Pandorabots as a platform to process text input from users so that chatbots can direct users to type according to the patterns and knowledge contained in the chatbot. There are two kinds of chatbots created in this study, namely text-based interaction and button-based interaction chatbots. The chatbot test uses 20 data samples in the form of questions and answers from Elementary School subject matter grades 1 to grade 6. Chatbots using AIML can only answer questions that are relevant and according to patterns in AIML. To optimize the performance of text chatbots, we recommend using large amounts of data. Whereas Chatbots with UI Buttons should use less data to work optimally. Keywords— AIML, button-based, chatbot, Pandorabots, elementary school, text-based Chatbot merupakan sebuah percakapan virtual yang dapat menerima input berupa suara atau tulisan. Sebuah chatbot dapat merupakan chatbot generative atau retrieval. Pembuatan kedua chatbot tersebut memberikan kesempatan untuk pengguna menulis teks dengan bebas. Terkadang memberikan kebebasan mengetik kalimat dengan bebas dapat menghasilkan jawaban yang tidak sesuai dengan keinginan pengguna. Ada beberapa cara agar pengguna dapat diarahkan untuk menuliskan teks dalam kolom chat. Penelitian ini bertujuan untuk mengembangkan aplikasi chatbot yang dapat digunakan sebagai media tanya-jawab materi pelajaran untuk siswa Sekolah Dasar secara terstruktur. Chatbot yang dikembangkan berbasis AIML (Artificial Intelligence Markup Language) menggunakan Pandorabots sebagai platform untuk memproses input teks dari pengguna sehingga chatbot dapat mengarahkan pengguna untuk mengetikan sesuai pola dan pengetahuan yang ada didalam chatbot. Terdapat dua macam chatbot yang dibuat pada penelitian ini yaitu text-based interaction dan button-based interaction chatbot. Pengujian chatbot menggunakan 20 sampel data berupa soal dan jawaban dari materi pelajaran Sekolah Dasar kelas 1 sampai dengan kelas 6. Chatbot dengan menggunakan AIML hanya dapat menjawab pertanyaan yang relevan dan sesuai dengan pola pada AIML. Untuk mengoptimalkan kinerja Chatbot text, sebaiknya data yang digunakan berjumlah besar. Sedangkan Chatbot dengan UI Button sebaiknya menggunakan data yang sedikit untuk dapat bekerja secara optimal. Kata Kunci—AIML, button-based, chatbot, Pandorabots, sekolah dasar, text-based